2022
DOI: 10.1002/ejic.202200119
|View full text |Cite
|
Sign up to set email alerts
|

Green Phosphorescent Zn(II) Halide Complexes with N,N,N′,N′‐tetramethyl‐P‐indol‐1‐ylphosphonic Diamide as Ligand

Abstract: Tetrahedral Zn(II) complexes having general formula [ZnX 2 {O=P-(NMe 2 ) 2 Ind} 2 ] (X = Cl, Br, I, NCS) were isolated from the reaction between the indol-1-yl substituted phosphoramide N,N,N',N'tetramethyl-P-indol-1-ylphosphonic diamide O=P(NMe 2 ) 2 Ind and anhydrous Zn(II) precursors under mild conditions. The structures of the three halide derivatives were ascertained by single-crystal X-ray diffraction. The bromo-and iodo-derivatives revealed to be appreciably luminescent in the green region upon excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…The nonradiative deactivation of the 1 LLCT­(CN) state might be related to somewhat weaker π-electron density-accepting properties in the excited states of N -heterocyclic carbenes compared to cAAC, which results in higher LLCT excitation energies for 8 and makes the 3 LC­(bdt) state accessible. Although a couple of recently published articles reported the population of triplet excited states in the case of Zn II molecules, such a photophysical behavior remains uncommon for the complexes based on light and earth-abundant zinc metal. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The nonradiative deactivation of the 1 LLCT­(CN) state might be related to somewhat weaker π-electron density-accepting properties in the excited states of N -heterocyclic carbenes compared to cAAC, which results in higher LLCT excitation energies for 8 and makes the 3 LC­(bdt) state accessible. Although a couple of recently published articles reported the population of triplet excited states in the case of Zn II molecules, such a photophysical behavior remains uncommon for the complexes based on light and earth-abundant zinc metal. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Another interesting metal center to be combined with [O=P]-donor ligands for optics is zinc. For instance, non-linear optical properties were observed for [ZnCl 2 (O=PPh 3 ) 2 ] [ 32 ], and Zn(II) halide complexes with N , N , N ′, N ′-tetramethyl- P -indol-1-ylphosphonic diamide showed intense green phosphorescence [ 33 ]. Given our interest in the preparation of luminescent metal complexes with phosphonates and cyclic organophosphorus compounds [ 34 , 35 , 36 , 37 ], we synthesized the two enantiomers of O=PPh(BINOL), and we started investigating the luminescent properties of the related Zn(II) and Mn(II) halide complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that 1-hydroxy-1H-imidazoles decorated with proton-accepting groups at position 2 of the imidazole ring and a pyridin-2-yl group at position 4 to assist the N 3 imidazolic atom in binding metal ions can act as ESIPT-capable ligands and coordinate Zn 2+ ions without deprotonation (HL p and HL q , see Scheme 2). Since Zn 2+ ions are known to be able to enhance the emission originating from the ligand-centered excited states due to so-called chela-tion-enhanced fluorescence (CHEF) effect, [125][126][127][128][129][130] their coordination by ESIPT-capable 1-hydroxy-1H-imidazoles led to a noticeable increase in the photoluminescence quantum yield (PLQY). 131,132 Moreover, the emission of the free ligands and complexes appeared to be tunable through the extension of the π-conjugation in the proton-accepting part of the molecule.…”
Section: Introductionmentioning
confidence: 99%